Analysis of Tourist Behaviour and Tourism Image in Hainan Province - Zhang, Xue (Transformations In Business & Economics, 2025)
With the development of tourism, theoretical research on tourist behaviour and tourist destinations is becoming more and more important, but currently, for the specific micro-tourism in Hainan Province, Theoretical research on context is still lacking. Therefore, this study takes tourists to Hainan, where they have published relevant travel notes as research objects. It also uses Python and other technologies to analyse the crawled network. The travel notes were systematically studied, focusing on exploring the behavioral characteristics of tourists in Hainan Province through the three dimensions of “regional relevance of tourist flow, travel motivation, and stay time” and the three dimensions of “cognitive image, emotional image, and conative image”. The research conclusion is: (1) The regional correlation of tourist flows in Hainan Province focuses on Sanya City. The four major bays of Hainan radiate outward; (2) The primary travel motivation of tourists coming to Hainan is the outdoor project experience, followed by duty-free shopping; (3) Although tourists coming to Hainan show a discrete distribution in terms of stay time, the average performance is 5-6-day multi-day stay experience type; (4) Among the six cognitive image categories of “tourist core attractions, tourist accommodation, tourist transportation, tourist entertainment, tourist shopping, and tourist food”, tourists visiting Hainan Province have the perception of core tourism attractions such as “climate and natural scenery” in tourist destinations as the strongest, and the perception of tourism products is the lowest; (5) The perception of the emotional image of tourist destinations in Hainan Province is mostly positive-oriented. Relatively speaking, there are relatively few negative perceptions, which are mainly concentrated on the three aspects of “accommodation, transportation, and integrity”; (6) Hainan Province’s tourist destinations. Conative image perception is mainly reflected in tourists’ strong recommendation intention.